Review of Nikos Potamianos, ed., Εκδοχές της ηθικής οικονομίας: Ιστορικές και θεωρητικές μελέτες : [Variants of moral economy: Historical and theoretical studies] - Efstathiou, Christos (Historein, 2023)
Review of Nikos Potamianos, ed., Εκδοχές της ηθικής οικονομίας: Ιστορικές και θεωρητικές μελέτες [Variants of moral economy: Historical and theoretical studies]. Rethymno: Institute for Mediterranean Studies, 2021. 399 pp.